Reflections from my Pedagogical Practice: Spontaneity versus Formalization - Carla Brenes-Jiménez (Universidad Nacional, Costa Rica, 2015)
This article describes an action research process undertaken with the main purpose of recognizing, re-evaluating and revising my pedagogical practices, together with the children I work with (two preschool groups: the first one is a preschool group I interacted with in 2012 comprised of 6 students ages 2 years and 3 months to 3 years and 3 months, while the second one is a group of 13 K-students ages 4 years and 3 months to 5 years and 3 months, with whom I shared in 2013).  This research process reflects the changes that drove me to a metamorphosis. In this process, evidence is given of findings, lessons learned and lessons unlearned which arose from the use of methodological strategies drawn from the naturalist paradigm. As part of the action research process, a change can be noted in my performance where I pass from a vertical epistemological position, in which my practices focused on memory, order and repetition, to a horizontal one in which children have the possibility of engaging in dialog, freely creating and sharing. The main tools to compile the information were filming and the classes shared with my students.